Rapidly Progressive Felty Syndrome After Sudden Discontinuation of Methotrexate: A Case Report and Review of Literature - Suaad Hamsho (16036276) (2023)
Felty syndrome (FS) is a disorder that develops after a long history of erosive rheumatoid arthritis and presents with splenomegaly and neutropenia. In addition to joint deformities, FS causes a variety of extra-articular manifestations such as vasculitis, skin lesions, and lymphadenopathy. FS is also reported to cause non-cirrhotic portal hypertension which may result in variceal bleeding. FS is usually treated by disease-modifying anti-rheumatic drugs (DMARDs) such as methotrexate. Herein, we report a case of rapidly deteriorating FS and a severe relapsing neutropenia only a few weeks after discontinuation of methotrexate and other available DMARDs. The patient presented with a fever and a multi-drug resistant gangrenous ulcer consistent with ecthyma gangrenosum. The patient was also found to have hepatosplenomegaly and portal hypertension. The case was managed with antibiotics and symptomatic treatments only as DMARDs were either unavailable or not affordable by the patient. However, the patient’s condition did not improve. This case highlights that DMARDs are considered an essential part of preventing infections due to FS neutropenia. Patients with FS should continue DMARDs for life to avoid the relapse of their condition.  Other Information Published in: International Medical Case Reports Journal License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.2147/imcrj.s365004